Mathematical physics e-module: A study of students' perception based on gender - Astalini Astalini; Darmaji Darmaji; Dwi Agus Kurniawan; Nadia Natalia Simamora (Universitas PGRI Kanjuruhan Malang, 2021)
Student’s perception is the student's assessment of something or information. The objective of this study was to discover how students' general perceptions and gender differences in electronic modules of mathematical physics. The research type is survey-based research with quantitative approach. The research population consists of physics education students from Universitas Jambi with the sample of 80 students from class A and class B. The data analysis techniques used in the study are descriptive statistics analysis and inferential data analysis using t-tests. The results showed that, overall, students have a positive perception with a Sig. (2-tailed) value of 0.011 < 0.005, which means that there is a significant difference in students’ perception. The perception of class A students with gender differences has a Sig. (2-tailed) value of 0.003, while the grade B students have a Sig. (2 tailed) values of 0.020 and 0.013. This means that class A and classs B students have a discernible difference of perception. Student’s perception may be used as a determining factor in the choice of learning materials. This research can be used as a guideline for the development of student perception assessment in the electronic module of Mathematical Physics in the future. The update of this study aims to compare students' perceptions of the overall online module of mathematics and gender differences.